The road to Jigalong: an exploration into the effect of altered landscapes in the Pilbara on place-identity - Rafferty, Fiona (Curtin University, 2021)
This exegesis investigates the significance of place, focusing on Pilbara landscapes that have been altered by European post-colonial pastoralism and extreme weather changes. Altered landscapes and place-identity are the major unifying themes of this practice-led research project, and the focus of this research is Ethel Creek Station, a working cattle station situated on approximately 400,000 hectares, in the East Pilbara region of Western Australia. Through creative practice in the visual arts my research examines the effect of these altered landscapes on place-identity.